Some vector optimization problems in Banach spaces with generalized convexity - Yu, Guolin; Liu, Sanyang (Computers & mathematics with applications (1987), 2007)
In this paper, we consider a vector optimization problem where all functions involved are defined on Banach spaces. New classes of generalized type-I functions are introduced for functions between Banach spaces. Based upon these generalized type-I functions, we obtain a few sufficient optimality conditions and prove some results on duality.